Polymers from Fossil and Renewable Resources : Scientific and Technological Comparison of Plastic Properties /: Scientific and Technological Comparison of Plastic Properties. (2019) - Ciardelli, F (Francesco); Bertoldo, Monica; Bronco, Simona; Passaglia, Elisa
No abstract available